Exposure to Aldehyde Cherry e-Liquid Flavoring and Its Vaping Byproduct Disrupt Pulmonary Surfactant Biophysical Function - Martin, Alexia; Tempra, Carmelo; Yu, Yuefan; Liekkinen, Juho; Thakker, Roma; Lee, Hayoung; de Santos Moreno, Berta; Vattulainen, Ilpo; Rossios, Christos; Javanainen, Matti; Bernardino de la Serna, Jorge (Environmental science & technology, 2024)
Over the past decade, there has been a significant rise in the use of vaping devices, particularly among adolescents, raising concerns for effects on respiratory health. Pressingly, many recent vaping-related lung injuries are unexplained by current knowledge, and the overall implications of vaping for respiratory health are poorly understood. This study investigates the effect of hydrophobic vaping liquid chemicals on the pulmonary surfactant biophysical function. We focus on the commonly used flavoring benzaldehyde and its vaping byproduct, benzaldehyde propylene glycol acetal. The study involves rigorous testing of the surfactant biophysical function in Langmuir trough and constrained sessile drop surfactometer experiments with both protein-free synthetic surfactant and hydrophobic protein-containing clinical surfactant models. The study reveals that exposure to these vaping chemicals significantly interferes with the synthetic and clinical surfactant biophysical function. Further atomistic simulations reveal preferential interactions with SP-B and SP-C surfactant proteins. Additionally, data show surfactant lipid-vaping chemical interactions and suggest significant transfer of vaping chemicals to the experimental subphase, indicating a toxicological mechanism for the alveolar epithelium. Our study, therefore, reveals novel mechanisms for the inhalational toxicity of vaping. This highlights the need to reassess the safety of vaping liquids for respiratory health, particularly the use of aldehyde chemicals as vaping flavorings.
Keywords: Adolescent; inhalation toxicology; e-cigarettes; chuťové esence; aldehydy; Flavoring Agents; Pulmonary Surfactants; povrchově aktivní látky; plicní surfaktanty; exposure and human health; Aldehydes; benzaldehydy; systémy dodávající nikotin elektronicky; Benzaldehydes; mladiství; vaping; lidé; Humans; Electronic Nicotine Delivery Systems; mechanistic toxicology; lung surfactant; Surface-Active Agents; Vaping